2015
DOI: 10.1093/gji/ggv307
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene uplift of Rhodes, Greece: evidence for a large tsunamigenic earthquake and the implications for the tectonics of the eastern Hellenic Trench System

Abstract: S U M M A R YSeveral large earthquakes in the Hellenic subduction zone have been documented in historical records from around the eastern Mediterranean, but the relative seismic quiescence of the region over the period of instrumental observation means that the exact locations of these earthquakes and their tectonic significance are not known. We present AMS radiocarbon dates from uplifted late Holocene palaeoshorelines from the island of Rhodes, showing that uplift is most consistent with a single large (M W … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 93 publications
0
34
0
Order By: Relevance
“…Such reverse faulting would also contribute to the longer-term Quaternary uplift by underplating Crete with subducted sediment. Similarly, late-Holocene palaeoshorelines and Quaternary marine terraces are observed on Rhodes (Gauthier , 1979;Pirazzoli et al, 1989), where their uplift is also attributed to offshore reverse faulting (Kontogianni et al, 2002;Howell et al, 2015).…”
Section: Vertical Motions In the Se Hellenic Subduction Zonementioning
confidence: 92%
See 2 more Smart Citations
“…Such reverse faulting would also contribute to the longer-term Quaternary uplift by underplating Crete with subducted sediment. Similarly, late-Holocene palaeoshorelines and Quaternary marine terraces are observed on Rhodes (Gauthier , 1979;Pirazzoli et al, 1989), where their uplift is also attributed to offshore reverse faulting (Kontogianni et al, 2002;Howell et al, 2015).…”
Section: Vertical Motions In the Se Hellenic Subduction Zonementioning
confidence: 92%
“…Shaw et al (2008) showed that the timing and distribution of uplifted late-Holocene palaeoshorelines on Crete (Figure 1) are consistent with coseismic uplift during a large (M W ∼ 8) earthquake in AD 365, on a reverse fault above the subduction interface that projects to the surface at the 3 km-deep escarpment known as the Hellenic Trench. Uplifted late-Holocene palaeoshorelines are also observed on Rhodes (Figure 1; Gauthier , 1979;Pirazzoli et al, 1989), where their presence has been attributed to a large earthquake sometime before 2000 BP (Stiros and Blackman, 2013;Howell et al, 2015), probably on a reverse fault that reaches the surface SE of Rhodes at the foot of a steep escarpment bounding the Rhodes Basin (Kontogianni et al, 2002;Howell et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Slip on faults of this type is also able to fit the spatial distribution of uplifted Holocene palaeoshorelines on Crete (e.g. Pirazzoli et al 1982;Shaw et al 2008) and Rhodes (Kontogianni et al 2002;Howell et al 2015) better than slip on a deeper subduction interface. Shaw et al (2008) used radiocarbon dating and elastic-dislocation modelling to show that Holocene uplift in SW Crete (up to 9 m) is consistent with uplift in a single earthquake on a 30 • -dipping reverse fault that projects to the surface in the Hellenic Trench (Fig.…”
mentioning
confidence: 99%
“…Coasts where uplift of Pliocene-Quaternary marine terraces has been observed are marked in white and blue, GPS velocities relative to stable Nubia are shown by red arrows and active volcanoes are marked by white triangles. The tsunamigenic reverse faults inferred by Shaw et al (2008) and Howell et al (2015) to explain uplift of Crete and Rhodes in large earthquakes are marked by thick red lines. Terrace locations are compiled from Kelletat et al (1976), Gauthier (1979), Angelier (1979b), Peters et al (1985), Armijo et al (1996), Zelilidis et al (1998), Stiros et al (2000), Kontogianni et al (2002), Gaki-Papanastassiou et al (2009, 2011, Karymbalis et al (2013), Gallen et al (2014) and our own fieldwork.…”
mentioning
confidence: 99%